1
$\begingroup$

I am studying this book and a particular line reads

$\int_{1-p}^1 \Phi^{-1}(u)du=${set $k=\Phi^{-1}(u)$}=$\int_{\Phi^{-1}(1-p)}^\infty k\phi(k)du$, where $\Phi$ and $\phi$ are the cumulative and density functions of the standard normal distribution.

and i cannot see how this is derived.

Does any kind person have the appetite to explain? Thanks in advance

$\endgroup$
1
$\begingroup$

Note that

$$\Phi^{-1}[\Phi(k)] = k$$

So subbing $u=\Phi(k)$, $du = \Phi'(k) dk = \phi(k) dk$, we get

$$\int_{1-p}^1 du \, \Phi^{-1}(u) = \int_{\Phi^{-1}(1-p)}^{\Phi^{-1}(1)} dk \, \Phi^{-1}[\Phi(k)] \Phi'(k) = \int_{\Phi^{-1}(1-p)}^{\infty} dk \, k\, \phi(k) $$

$\endgroup$
  • $\begingroup$ Thank you! Much appreciated! I didn't think of the first thing you wrote! $\endgroup$ – Trelokoritso Feb 17 '16 at 9:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.